2021
DOI: 10.21037/acs-2019-mv-169
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve-in-valve and valve-in-ring: tips, tricks, and outcomes

Abstract: Transcatheter aortic valve implantation is now a mainstay of treatment in patients with aortic stenosis who are considered intermediate, high and prohibitive risk for surgery. Extended use of this innovative platform in treating other conditions has led to its approval in treating degenerated aortic bioprosthesis. Similarly, use of transcatheter devices in treating degenerated mitral bioprosthesis and failed mitral valve repairs with annuloplasty rings has opened a potential alternative to surgery in these pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 20 publications
0
9
0
6
Order By: Relevance
“…Complete semirigid annuloplasty rings may also have characteristics suitable for future transcatheter valve-in-ring intervention. 26 The current series showed that, for all patients, the degree of recurrent MR increased slowly over time and tended to plateau at about 1+ or mild MR by 5-10 years (Figures 2 and 6A).…”
Section: Discussionmentioning
confidence: 55%
“…Complete semirigid annuloplasty rings may also have characteristics suitable for future transcatheter valve-in-ring intervention. 26 The current series showed that, for all patients, the degree of recurrent MR increased slowly over time and tended to plateau at about 1+ or mild MR by 5-10 years (Figures 2 and 6A).…”
Section: Discussionmentioning
confidence: 55%
“…Currently, the Sapien 3 (Edwards Lifesciences Incorporation, Irvine, California, USA) is used as the standard THV for most TMVIV interventions with good short-term outcomes ( 7 , 15 ). To avoid embolization, it is important to avoid parallel deployment and achieve conical deployment with an oversizing strategy ( 8 ). Unlike with the Sapien XT (Edwards Lifesciences Incorporation, Irvine, California, USA) ( 16 ), interventionists tend to select the proper Sapien 3 size selection following a slightly oversizing principle for its favorable extensibility.…”
Section: Discussionmentioning
confidence: 99%
“…In TMVIV, an oversizing strategy is preferred due to the risk of embolization resulting from high gradient pressure between the ventricle and atrium. However, excessive oversizing may be unfavorable, as it leads to under expansion of the transcatheter heart valve (THV) device, which increases the risk of leaflet pin-wheeling, device thrombosis, and decreased durability ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is not appropriate to perform extreme oversizing, as a significantly underexpanded transcatheter valve may lead to incorrect leaflet coaptation, elevated transvalvular gradient and limited durability. Under-expansion increases the risk of leaflet pin wheeling, possible thrombosis and decreases durability (39).…”
Section: Currently Available Transcatheter Devices For Failed Mitral Bioprosthesesmentioning
confidence: 99%
“…An angle of >15° for Sapien S3 (>20° for Sapien S3 Ultra) should raise the concern for post-implant paravalvular leak (PVL) (40). Although CT scans are emerging to be an important imaging modality in these patients, characterization of different bioprosthesis based on CT scans is not standardized and thus, they can only be used as an adjunct to the sizing information in the mitral VIV application (39).…”
Section: Pre-procedural Assessmentmentioning
confidence: 99%